Financing the BRAC Health Centres: their financial sustainability and cost-effectiveness - Khan, Suhaila H; Mahmud, Shah Noor; Karim, Fazlul; Afsana, Kaosar (BRAC Research and Evaluation Division (RED), 2020)
The Health ana Population Division (HPO) of BRAC aims to provide supportive secondary level health care services for the community through the BRAC Health Centres (BHCs) or Shushasthyos. The BHCs began operating in HPO areas in 1995. As of January 1998 there were 27 BHCs. All BHCs function through user fees in order to make the BHCs financially sustainable in the long run. HPD is endeavoring strategic planning in order to reduce donor dependence and meet the projected resource gaps through the implementation of certain systems such as, cost recovery and cost sharing through the BHCs, to ensure financial sustainability in the long run. The Research and Evaluation Division (RED) of BRAC aimed to evaluate how much cost recovery was occurring at the BHCs which contributed to BHCs' financially sustainability, and what modifications need consideration to support enhance this sustainability. This was a health facility based study done in 9 BHCs in three regions. Mymensingh, Bogra and Dinajpur. The variables considered for this study were related to cost. revenue, cost sharing and effects. The average or unit cost of operating a BHC was Tk. 422.092. The recurrent cost was Tk. 403 ,547 and capital cost was Tk. 18,545. Average income per BHC was Tk. 89,631. The cost recovery was 22% of recurrent costs and 21% of total costs. And if we considered the variables similar to HPD then cost recovery was 35% of recurrent costs and 33% of total costs. 23% of the indicators mentioned in the monthly disease profile cover gynaecologicals conditions. These constitute about 11% of the total general diseases being identified and/or treated at the BHCs. This is only possible due to having a facility such as a BHC. The unit cost per patient visit was Tk. 93. Some interventions, such as ANC and GM done at BHCs seemed to be cheaper compared to previous findings of WHOP and RDP-PHC.